Evaluation of General Synthesis Procedures for Bioflavonoid–Metal Complexes in Air-Saturated Alkaline Solutions - Yao, Yuanyong; Zhang, Meng; He, Laibing; Wang, Yunyang; Chen, Shixue (Frontiers in Chemistry, 2020)
Due to bioflavonoids non-stabilized in air alkaline solution, the general synthetic procedure for synthesis of bioflavonoids metal complexes in air alkaline solution was considered to be doubtful. In this study, dihydromyricetin (DHM) acting as a representative example of bioflavonoids was selected to make a complexation with varied transition metal ions in air alkaline solution to form DHM metal(II) complexes, as following the general synthetic procedure of bioflavonoids metal complexes. After characterized well by some technologies, their metal complexes were authorized to be hydrolyzed for observing stabilization of DHM of DHM-M(II) complexes under acidic conditions, via HPLC. Subsequently, some of synthetic factors, e.g., metal ion, alkalinity and refluxing time were solely and respectively investigated by UV-Vis spectrophotometer or HPLC in affecting dihydromyricetin stabilization. Finally, by means of EPR spectroscopy, dihydromyricetin and its analogues were observed with the help of DMPO (5,5-dimethyl-1-pyrroline-N-oxide) capable to form a relatively stable free radical adduct in air alkaline solution. As a result, the results demonstrated that dihydromyricetin metal(II) complexes after undergoing hydrolysis in acidic solution is proved not to be a single content of DHM in LC spectra by HPLC, indicating that partial dihydromyricetin could make a reaction in the process of synthesizing dihydromyricetin metal(II) complexes. Simultaneously, both of transition metal ion and alkalinity were testified to be predominant synthetic factors of dihydromyricetin metal(II) complexes, because of free dihydromyricetin stabilization affected seriously. Furthermore, dihydromyricetin and its analogues were witnessed to be generators of superoxide-anion radical in air alkaline solution, with observing typical signals of DMPO-OO·- adduct by EPR. And their capacities of generating superoxide anion were close to numbers and/ or locations of hydroxyl groups attached to molecule skeleton or their configurations. Interestingly, dihydromyricetin reacted with superoxide anion can be transformed into myricetin, which is involving in a C3 H atom of DHM abstracted by O2.- in mechanism. Therefore, the general synthetic procedure for synthesis of bioflavonoids metal complexes in air alkaline solution should be unreasonable.